Antimicrobial resistance of Streptococcus spp. isolated from bovine clinical mastitis in Argentinean Mar y Sierras Region Dairy Farms - Bottini, E. (2022)
Streptococcus dysgalactiae, and S. uberis are the most prevalent Streptococcus species isolated from clinical\nmastitis. Most of all antimicrobials administered on dairy farms are for treating mastitis. Considering that antimicrobial resistance can vary between regions, it is crucial to monitor the susceptibility of microorganisms to antimicrobials used. Particularly, it is known that clinical mastitis caused by S. uberis frequently do not respond to antimicrobial therapy and that this pathogen causes recurrent infections. The general aim was to evaluate the antimicrobial susceptibility of S. uberis and S. dysgalactiae isolates from 23 dairy farms located in the Cuenca Mar y Sierras, Argentina, for the main antimicrobials used in this region, and characterize the dairy farms from which the pathogens come. A total of 39 S. uberis and S. dysgalactiae strains were isolated and tested for susceptibility to 5 antibiotics using a disc diffusion method. Results showed frequencies of AMR to tetracycline of 26 %, pirlimycin 18 %, rifaximin 15 %, penicillin 8 %, and kanamycin 5 %, the detection of resistance to all the antibiotics in S. uberis, and that the multi-resistant isolates belonged to dairy farms that carry out antimicrobial treatments in an empirical manner.